Knowledge of mucin immunostaining status of "nuclear inverse polarity papillary lesions lacking myoepithelial cells" may prevent unnecessary breast surgery: experience of two cases. Issue 2 (February 2023) - Tajima, Shinya; Kishimoto, Keiko; Maeda, Ichiro; Aida, Yoshio; Kazama, Akio; Takagi, Masayuki
We previously reported on two women with breast lesions in whom radiological examination could not exclude malignancy. In both cases, mastectomy was performed, and histological analyses revealed papillary lesions lined by fibrovascular stroma and nuclear inverse polarity. Hematoxylin–eosin, p63, and calponin staining indicated an absence of myoepithelial cells. However, it was concluded that the lesions had been non-malignant. These women have now been under long-term surveillance (74 months for one case and 62 months for the other) and have had no disease recurrence. Mucin (MUC)1, MUC2, MUC4, MUC5AC, MUC5B, and MUC6 immunostaining has also been performed in these women to investigate further whether their tumors were malignant or benign. In both cases, the tumors were only positive for MUC1 in apical luminal apical cells, as in normal breast tissue. MUC5B immunostaining, even when weak, can detect early breast cancer but was completely negative in our two cases. Therefore, both tumors were considered benign. Our findings in these cases suggest that nuclear inverse polarity papillary lesions lacking myoepithelial cells are benign. This knowledge should decrease the number of unnecessary operations performed for this tumor and their negative impact on patients' quality of life.